Assessment of cytotoxicity potency of paclitaxel in combination with Clinacanthus Nutans extracts on human MDA-MB-231 breast cancer cells - Nur Hasnieza Mohd Rosli,; Chan, Kok Meng; Fariza Juliana Nordin,; Lek, Mun Leong; Nur Syazwani Abdul Aziz,; Nor Fadilah Rajab, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Clinacanthus nutans (C. nutans) leaf extracts have been widely used by cancer patients in Malaysia and local practice claims a cure to cancer. There were several studies done to determine the cytotoxicity potency of C. nutans extracts on various types of cells. However, there is still lacking on the knowledge regarding the combination effect of C. nutans with anticancer drugs. Thus, the study was carried out to determine the cytotoxicity potency of C. nutans extracts and paclitaxel (PTX) alone and, in combination on MDA-MB-231 cells. The cells were treated with 100% ethanol extract of C. nutans (CNE) and water extract of C. nutans (CNA), PTX and combination of both extracts and PTX for 72 hours and the cytotoxic activity was determined using SRB assay. Result showed that CNE had little cytotoxic activity, whereas CNA showed no cytotoxic activity on MDA-MB-231 cells. For combination treatment of C. nutans extracts and PTX, only CNE showed significant enhanced PTX-induced cytotoxicity (p < 0.05), meanwhile CNA inhibited PTX-induced cytotoxicity significantly (p < 0.05). As a conclusion, CNE was able to increase PTX potency to inhibit the viability of MDA-MB-231 cells.